Angiotensin II signaling through the AT1a and AT1b receptors does not have a role in the development of cerulein-induced chronic pancreatitis in the mouse - Ulmasov, Barbara (Am J Physiol Gastrointest Liver Physiol, 2010)
The intraorgan renin-angiotensin system (RAS) plays an important role in the pathophysiology of a variety of diseases and has been implicated in fibrogenesis. The role of RAS in the development of chronic pancreatitis is not well established. The blockade of RAS in rat models with angiotensin-converting enzyme inhibitors (ACEi) or angiotensin receptor 1 (AT1) blockers (ARBs) mostly have reduced pancreatic inflammation and fibrosis with a few exceptions. At the same time, the use of ACEi and ARBs in humans is associated with a modest risk of acute pancreatitis. The aim of this study was to elucidate the effect of the AT1 signaling pathway in the development of pancreatitis using AT1a- and AT1b-deficient mice as well as the ARB losartan. Chronic pancreatitis was induced by repetitive cerulein administration in C57BL/6J wild-type (WT) and AT1a- and AT1b-deficient mice (AT1a−/− and AT1b−/−), and pancreatic injury was assessed at day 10. Pancreatic weight of cerulein treated groups was significantly reduced. There was severe parenchymal atrophy and fibrosis assessed by histological examination. Fibrosis was accompanied by activation of pancreatic stellate cells (PSC) evaluated by Western blot analysis for α-smooth muscle actin. No differences were seen between cerulein-treated WT, AT1a−/− , AT1b−/− mice, or losartan treated-WT mice with regards to morphological or molecular alterations induced by cerulein. Our results demonstrate that AT1a and AT1b receptor pathways do not seem to be essential for the development of pancreatitis in the mouse model of pancreatitis induced by repetitive cerulein injury.